(3cJGH GdESJceGd dHjGf LejY eG jCJi aj cJGH Gddg YR hLd aj ePgH GdbQGA GdSHYI aj GdJaNje hGdEeGdIs - (3YHO GdefYe Hf YHjO Gddg Hf ZdHhf Hf GdeHGQc, CHh GdWqjH, J (B389 (3g` s
(3ChdgG (B:s
(3bGd CHh GdWjH Hf ZdHhf GdebQi GdMeO ddg GdPi Ndb GdCTjGA cdgG hGdHQjGJ hGYde CjgG GdfGXQ ai cJGHi gPG Cfi fXQJ Edi GdWGdHjf GdbQGAGJ s
(3BNQgG (B:s
(3GdEeGdI (B: (3aUd ai Gdhba hgh eG hba Ydjg GdcSGFi Ydi eG bHd gG GdJCfjK fMh fYeg hQMeg hehJg agPG LejY eG ai cJGH Gddg JYGdi ef GdENJdGa ai GdJaNje hGdEeGdI heG cGf Hjf GddaXjf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs